2008
DOI: 10.1007/s10714-008-0694-5
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological model with interactions in the dark sector

Abstract: A cosmological model is proposed for the current Universe consisted of non-interacting baryonic matter and interacting dark components. The dark energy and dark matter are coupled through their effective barotropic indexes, which are considered as functions of the ratio between their energy densities. It is investigated two cases where the ratio is asymptotically stable and their parameters are adjusted by considering best fits to Hubble function data. It is shown that the deceleration parameter, the densities… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
63
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 43 publications
0
63
0
Order By: Relevance
“…This important result can be clarified in the following way. The system (52), in the absence of interaction, is equivalent to the following system for the relative densities Ω dm and Ω de…”
Section: Phenomenology Of Interacting Modelsmentioning
confidence: 99%
“…This important result can be clarified in the following way. The system (52), in the absence of interaction, is equivalent to the following system for the relative densities Ω dm and Ω de…”
Section: Phenomenology Of Interacting Modelsmentioning
confidence: 99%
“…This best fit value for the transition redshift z acc = 0.805 is significantly higher than that obtained in [73] at 1σ CL analyzing distinct databases and in a model-independent way. However, it is typical for models with interactions in the dark sector [57,[74][75][76][77][78].…”
Section: And Inmentioning
confidence: 99%
“…Only hypotheses on their nature exist, most of them assuming that DM and DE are physically unrelated and the similarity in their energy densities (the so called problem of Cosmological Coincidence) is a purely accidental fact [14][15][16][17]. But interactions between DM and DE might alleviate the problem, keeping close values for their densities up to large redshifts as has been shown in a lot of work [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. The interactions between DE and DM appear to be favored in several works, for instance, by Bertolami et al [34][35][36][37] through studies on the Abell Cluster A586, and Abdalla et al [38] where they found the signature of interaction between DE and DM by using optical, X-ray and weak lensing data from 33 relaxed galaxy clusters.…”
mentioning
confidence: 99%
“…Most of the hypotheses assume that DM and DE are physically unrelated and the similarity in their energy densities is purely accidental. But interactions between DM and DE might alleviate the problem, keeping close values for their densities up to large redshifts as has been shown [6][7][8][9][10][11][12][13][14]. Attempts to unify DE and DM is not a stopping process.…”
Section: Introductionmentioning
confidence: 99%